Schizophyllum leprieurii and the Schizophyllum umbrinum lineage (Agaricales, Basidiomycota) in Argentina - Robledo, Gerardo L.; Popoff, Orlando E.; Amarilla, Leonardo D.; Moncalvo, Jean-Marc (Lilloa, 2014)
Robledo, Gerardo L.; Orlando F. Popoff; Leonardo Amarilla; Jean-Marc Moncalvo; Carlos Urcelay. 2014. “Schizophyllum leprieurii and the Schizophyllum umbrinum lineage (Agaricales, Basidiomycota) in Argentina”. Lilloa 51 (1). During the survey of wood decaying fungi in NW and Central Argentina, particular collections of Schizophyllum were found that macromorphologically (small brown basidiomata with orange-brown lamellae) resemble Schizophyllum umbrinum. On the basis of molecular evidence (ITS and LSU rDNA sequence analysis) and micromorphological examination it was found that they represent two species: Schizophyllum leprieurii Linder and Schizophyllum cf. umbrinum. Schizophyllum leprieurii Linder is a new record for Argentina and represents the southernmost and an extra tropical record of the species. Our results showed that S. leprieurii and S. cf. umbrinum are monophyletic within the Schizophyllum umbrinum linage, a group in need of modern taxonomic revision